Isolated Single Iron Atoms Anchored on N‐Doped Porous Carbon as an Efficient Electrocatalyst for the Oxygen Reduction Reaction. (12th April 2017) - Chen, Yuanjun; Ji, Shufang; Wang, Yanggang; Dong, Juncai; Chen, Wenxing; Li, Zhi; Shen, Rongan; Zheng, Lirong; Zhuang, Zhongbin; Wang, Dingsheng; Li, Yadong
Abstract: The development of low‐cost, efficient, and stable electrocatalysts for the oxygen reduction reaction (ORR) is desirable but remains a great challenge. Herein, we made a highly reactive and stable isolated single‐atom Fe/N‐doped porous carbon (ISA Fe/CN) catalyst with Fe loading up to 2.16 wt %. The catalyst showed excellent ORR performance with a half‐wave potential ( E 1/2 ) of 0.900 V, which outperformed commercial Pt/C and most non‐precious‐metal catalysts reported to date. Besides exceptionally high kinetic current density ( J k ) of 37.83 mV cm −2 at 0.85 V, it also had a good methanol tolerance and outstanding stability. Experiments demonstrated that maintaining the Fe as isolated atoms and incorporating nitrogen was essential to deliver the high performance. First principle calculations further attributed the high reactivity to the high efficiency of the single Fe atoms in transporting electrons to the adsorbed OH species.